Traces of Violence in the GAM & NKRI Conflict in Aceh: Portraits of Victims and Their Impact - Ula, Dirta Wardatul; Afdilla, Kurnia; Razika, Faiza; Amanda, Julia; Sarifah, Sarifah; Shintya, Inka; Suzanna, Ella (Program Studi Psikologi Fakultas Kedokteran Universitas Malikussaleh, 2024)
The prolonged and complex conflict in Aceh has left significant impacts on the community, particularly on the victims who endured violence and fear. This study aims to explore the psychological effects experienced by the victims of the GAM (Gerakan Aceh Merdeka) and Indonesian government conflict, and to understand how these effects persist to this day. Utilizing a qualitative narrative approach with a biographical type, this research involves an interview with a victim who directly experienced violence during the conflict. The findings reveal that psychological trauma, such as fear of gunfire, explosions, and objects associated with the conflict, remains deeply ingrained in the victims memory. Even the sound of fireworks and firecrackers triggers anxiety, and daily activities, such as frying fish, become challenging due to the popping sounds reminiscent of past violence. The implications of this research highlight the importance of addressing psychological trauma for conflict victims, as well as the need for policies focused on psychosocial recovery. Sustainable solutions must continue to be developed to support recovery and peace in Aceh and to prevent long-term effects for future generations.